2010
DOI: 10.1111/j.1469-8986.2009.00881.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of face inversion on intracranial and scalp recordings of event-related potentials

Abstract: The face inversion effect (FIE) refers to a disproportionate disruption of the processing of face information by inverting faces. We investigated the FIE in epilepsy patients by simultaneous intracranial and scalp recordings of event-related potentials (ERPs). In scalp recordings, a typical FIE on ERPs was observed with increased latencies and amplitudes of the positive counterpart of the occipito-temporal N170, namely, the vertex positive potential (VPP), in response to inverted faces. Similar amplitude and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
58
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 72 publications
(142 reference statements)
7
58
0
Order By: Relevance
“…Recent results extend this notion further and suggest that the processing of inverted faces is more similar to the processing of non-face objects than to that of upright faces (Haxby et al, 1999;Rossion et al, 2000;Rosburg et al, 2010;Kloth et al, 2013), presumably due to the enhanced functional connectivity of the face specific areas with higher-order object sensitive areas (Nguyen et al, 2013). These findings could also explain the increased bold response to inverted as opposed to upright faces, which we observed in the object sensitive LO.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Recent results extend this notion further and suggest that the processing of inverted faces is more similar to the processing of non-face objects than to that of upright faces (Haxby et al, 1999;Rossion et al, 2000;Rosburg et al, 2010;Kloth et al, 2013), presumably due to the enhanced functional connectivity of the face specific areas with higher-order object sensitive areas (Nguyen et al, 2013). These findings could also explain the increased bold response to inverted as opposed to upright faces, which we observed in the object sensitive LO.…”
Section: Discussionsupporting
confidence: 66%
“…Therefore, it seems that inversion leads to qualitatively different processing of stimuli belonging to categories of high expertise, such as faces. In line with this specificity, recent behavioral electrophysiological and neuroimaging results suggest that the visual system processes inverted faces more similarly to nonface objects than to upright faces (Haxby et al, 1999;Rossion et al, 2000;Rosburg et al, 2010;Kloth et al, 2013). Therefore, we reasoned that if the face-specificity of P(rep) effects is due to the unique (holistic/configural) processing steps of an upright face then stimulus inversion, a manipulation that interrupts these processing steps, should interfere with the modulatory effects of P(rep) as well.…”
Section: Introductionmentioning
confidence: 87%
“…Previous studies in the normal developmental aspects of the N170 throughout childhood, demonstrating preserved symmetry (Taylor et al, 1999), suggest that an abnormal left hemisphere function it is the most likely explanation for the inter-hemisphere N170 difference. Rosburg et al (2010) studied the effect on the vertex positive potential (VPP) of face inversion in a heterogeneous sample of epileptic patients undergoing surgery for epilepsy. Lateralization effects were not searched for, and no correlation of the findings with the particular type of epilepsy was performed.…”
Section: Discussionmentioning
confidence: 99%
“…The delay in N170 peak latency to inverted or scrambled face images may be caused by a delay in the process of categorising these images as faces. In contrast, the enhancement of N170 amplitudes to inverted or scrambled as compared to upright intact faces could be linked to the recruitment of additional non-face selective neural populations by face images that do not match the canonical upright face template (e.g., Rosburg, Ludowig, Dampelmann, AlbaFerrara, Urbach, Elger, et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This might reflect a reduction in the specificity of functional specialization within ventral visual areas for upright faces, resulting in equally large or even larger N170 components for intact upright faces as compared to inverted or scrambled faces. For example, a general impairment in the face-specificity of perceptual processing in DP could result in a tendency for upright faces to activate object-selective areas that would otherwise only be activated by non-face objects or by inverted or scrambled face images with properties that deviate from the prototypical spatial template for upright faces (e.g., Rosburg et al, 2010). A recent fMRI study (Zhang, Liu, & Xu, 2015) has found converging evidence for a lack of sensitivity to the configuration of face parts within the core face processing network in DP.…”
Section: Discussionmentioning
confidence: 99%